PROBLEMATIKA PENERAPAN BAGI HASIL DALAM PENAMBANGAN EMAS - Arma Desi Saputri; Alfadli Alfadli; Supardi Dwimaputra (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
the application of a profit-sharing system carried out by the community by applying the concept of profit-sharing by calculating profits based on net results and calculated based on agreement. However, the determination of the agreement was not made in writing and there were no witnesses. This creates anxiety for the parties concerned because they are afraid that there will be no evidence in the event of fraud. This thesis aims to find out the profit sharing mechanism in gold mining, to find out the profit sharing system in the muamalah fiqh perspective, and to know the concept of profit sharing in gold mining in the muamalah fiqh perspective. The data used are primary data and secondary data. Primary data were obtained from informants using observation, interviews and documentation techniques. Secondary data obtained from books, theses, theses and laws and regulations. The data obtained is processed using data presentation in the form of reduction, display, and verification. The research resulted in the following conclusions. First, the profit sharing mechanism for gold mining is determined based on profit sharing. Second, the concept of the contract used is the mudharabah musytarakah contract. Third, the gold mining profit sharing system is not fully in accordance with the mudharabah concept because in practice there are still several provisions that have not been fulfilled in accordance with the provisions of Islamic law.